2006
DOI: 10.1002/sia.2240
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the interface manipulation in SiC(100) on Si(100) with isovalent impurities

Abstract: SIMS and transmission electron microscopy studies revealed an improvement of the SiC/Si(100) heterostructure properties if isovalent atoms with larger atomic dimensions than Si and C were used to modify the interface. The Ge incorporation at the interface suppresses the outdiffusion of Si from the substrate to the surface of the growing SiC layer and, therefore, impedes surface and interface roughening as well as the formation of voids at the SiC/Si interface. SIMS measurements obtained revealed that Ge remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…As a consequence, degraded electrical properties of the grown SiC layer and the SiC/Si heterojunction are observed. As shown previously, the interdiffusion can be reduced or suppressed if germanium is deposited prior to the SiC growth, [7,8] and the electrical properties of the SiC/Si heterojunction improves. [3] In this article we report on the effect of Ge predeposition on the early stages of the SiC formation by carbonization, as investigated by spectroscopic methods.…”
Section: Introductionmentioning
confidence: 57%
“…As a consequence, degraded electrical properties of the grown SiC layer and the SiC/Si heterojunction are observed. As shown previously, the interdiffusion can be reduced or suppressed if germanium is deposited prior to the SiC growth, [7,8] and the electrical properties of the SiC/Si heterojunction improves. [3] In this article we report on the effect of Ge predeposition on the early stages of the SiC formation by carbonization, as investigated by spectroscopic methods.…”
Section: Introductionmentioning
confidence: 57%
“…This is due to the fact that the surface roughness scales with the grain size of the nuclei and therefore, with the nucleation density [18]. The roughness behaviour of the carbonized layer is replicated during the subsequent epitaxial growth [19], i.e. the morphology of the 3C-SiC(100) pseudo-substrate determines the morphology the of the heterosystem.…”
Section: Contributedmentioning
confidence: 99%
“…If the Ge coverage of the surface is properly chosen, the nucleation of the SiC on Si can be designed in such a way that the formed SiC layer exhibit a minimum surface roughness and interface width. This optimum is strongly connected to a minimum of SiC grain size in the converted layer and led to a reduced residual stress [2] and lower surface roughness [19]. The improvements in structure and morphology of the pseudosubstrates are achieved at the expense of reduced SiC thickness.…”
Section: Sims Depth Profile Simulationmentioning
confidence: 99%
“…The reports on Ge pre-deposition before carbonization are more numerous. It is shown that Ge remains at the SiC/Si interface and/or in-diffuses inside the Si substrate [76,77]. It modifies SiC nucleation mechanism [78,79] and, for optimal Ge amount, leads to reduced residual stress inside the thin 3C-SiC layer, lower Si out-diffusion from the substrate and also reduction of other polytypes inclusions [80].…”
Section: Ge Addition To 3c-sic Growth On Siliconmentioning
confidence: 99%